Analisis IHSG dan Kurs Rupiah Sebagai Salah Satu Indikator Ekonomi Indonesia - Achmad, Noor (Jurnal Ilmiah Ranggagading (JIR), 2001)
Economic observer and stock exchange analyst use IHSG and rupiah exchange rate to US dollars as parameter for Indonesiaâs economic growth and to measure the cabinetâs purpose IHSG and rupiah exchange rate to US dollars as parameter for Indonesiaâs economic growth and to measure the cabinetâs performanceâs . In Indonesiaâs uncertainty is so high . Whatever the cause has given enough space for the speculators. The speculatorâs most fertile field is the stock exchange and the money market (i.e. foreign exchange). They have been able to re-engineer the market, the rupiahâs rate and IHSG to run the way they want it to. Like most Asian speculatorâs, they run short term using momentâs created through rumors and issues that perpetuate uncertainties. Speculative late of return whether it in foreign exchange market or the stock exchange is so high the Bankâs of Indonesia effort to maintain the rupiah by the giving the Bank Indonesiaâs certificate (SBI)an interest rate o 17,6% was not succeed. Miranda Gultom final also admitted that the Bank of Indonesia certificate was not able to control rupiah and also to press the base money into 110.5 trillion rupiah. The article is a result of an observation to the moment of rupiah rate to US dollars and the HISG started January 1996 up until July 2001. IHSG movement correlates to the rupiah anomalically . The test result show that during the crisis period where uncertainty magnitude was high, both HISG and rupiah rate were reflecting the market that was moved by speculator rather than Indonesiaâs economic condition .As long as the uncertainty magnitude is still in the high level, Than the rupiah rate and IHSG cannot be used as parameter for economic measurement.